Independensi Wali Amanat Dalam Memberikan Perlindungan Kepada Para Pemegang Obligasi - ., Jono (LAW REVIEW, 2004)
A bond is a debt instrument of the issuer that contains a promise to pay interest or such other obligations and the redemption of the loan executed at due date. Usually, issuer is a pointed Commercial Bank to be Trustee and they will make a contract. The contract binds bond holders. The purpose of pointing the trustee is to protect bond holder s interest. Trustee is demanded to stand independently. These circumstances related Â with the function of trustee to representation and protecting bond holders interest. This article will explain about trustees independent action to accomplish its function.